South Korea's Reunification Think Tanks: The Development of a Marketplace for Ideas - Ralph Wrobel (Asien - The German Journal on Contemporary Asia, 2014)
In contrast to Germany South Korea has for years been continuously preparing for national reunification. As a result, alongside the Ministry of Unification a number of think tanks, research institutes, and other organizations have also been established in South Korea. After years of the dominance in the country of state-run, security-orientated think tanks in the wake of German reunification, a new structure of reunification think tanks has recently evolved. Nowadays, besides the 22 Korean think tanks themselves, seven foreign think tanks are also active in this field of research. Therefore, the market of ideas concerning reunification research can be described as a broad but open oligopoly. Additional restrictions on the competition of ideas are generated by the two different overlapping subsystems of society: science and politics. South Korean reunification think tanks compete with each other on two fronts: the market of ideas and the market of financial resources. Because the South Korean government is the main financial donor to reunification research in South Korea, several think tanks have only limited independence. However, a growing pluralistic structure within reunification-oriented think tanks gives us reason to expect increasingly pluralistic research results as well.
Keywords: Z; 300; Korean Reunification; think tanks; Koreanische Wiedervereinigung; Denkfabriken